Anxiety and depression in women with breast cancer: Social and clinical determinants and influence of the social network and social support (DAMA cohort). (August 2018) - Puigpinós-Riera, R.; Graells-Sans, A.; Serral, G.; Continente, X.; Bargalló, X.; Domènech, M.; Espinosa-Bravo, M.; Grau, J.; Macià, F.; Manzanera, R.; Pla, M.; Quintana, M.J.; et al.
Highlights: In the cohort Dama 15% of women has some degree of depression and 485% has some degree of anxiety. Younger women suffer more anxiety. In contrast, the rate of depression is lowest in younger women (<50 years). Low emotional support and low social network are the risk factor to be more symptoms of some mental disorders. The social class and employment status are the risk factors to be more symptoms of some mental disorders. Women with relapse are more probability to be more symptoms of some mental disorders. Abstract: Background: Anxiety and depression are the most prevalent mental health pathologies among women with breast cancer. Social, clinical and contextual variables may influence emotional stress among women with breast cancer. The aim of this work is to study anxiety and depression in a cohort of women diagnosed with breast cancer between 2003 and 2013 in Barcelona. We evaluate social and clinical determinants. Methods: We performed a mixed cohort study (prospective and retrospective) using a convenience sample of women diagnosed with breast cancer. The information sources were the Hospital Anxiety and Depression questionnaire and hospital medical records. Dependent variables were anxiety and depression; independent variables were social class, age, employment status, tumour stage at diagnosis, time since diagnosis, social network and social support. We performed a descriptive analysis, a bivariate analysis, and a multivariate logistic regression analysis. Results: A total of 1086 (48.6%) women had some degree of anxiety-related problem. As for depression. In the case of depression, 225 (15%) women had some degree of depression-related problem. Low emotional support and social isolation were clear risk factors for having more anxiety and depression. Low social class was also a risk factor, and age also played a role. Discussion: Our results show that women long period of cancer survival have high prevalences of anxiety than depression, and this prevalence of anxiety is higher than the general population. In addition, we found inequalities between social classes and the isolation and social support are worse too in low social class.